(untitled) (Research, Society and Development, 2021)
The increase in life expectancy of the Brazilian population has allowed people to achieve greater longevity. This fact does not necessarily imply a healthy old age, since at this stage of life the presence of non-communicable chronic diseases, including Alzheimer’s disease, is quite common. Physiotherapy is an important tool in improving the quality of life and in the functional and motor reestablishment of Alzheimer’s patients, with the objective of delaying the progress of the disease, preserving motor functionality as close to normal as possible, working with a multidisciplinary team, guiding family members and caregivers of dementia patients. The aim of the present study was to specify the most used physical therapy interventions during the rehabilitation of patients with Alzheimer’s Disease and to describe how physical therapy interventions contribute to the improvement and maintenance of the patients’ functional performance. This is a descriptive and qualitative bibliographic research. Searches were performed using the Virtual Health Library (BVS), PEDro and PUBMED databases and the descriptors used were: Alzheimer, Physiotherapy, Alzheimer’s Dementia, Rehabilitation, Physioteraphy. Seven scientific articles were selected for analysis and discussion of the results that met the inclusion and exclusion criteria for the research. From the results obtained, it can be concluded that exercise-based therapy is effective in non-pharmacological treatments for patients diagnosed with Alzheimer’s Disease.